2005
DOI: 10.1089/ten.2005.11.90
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Reorganization in Response to Mechanical Load Increases Functionality

Abstract: In the rapidly growing field of tissue engineering, the functional properties of tissue substitutes are recognized as being of the utmost importance. The present study was designed to evaluate the effects of static mechanical forces on the functionality of the produced tissue constructs. Living tissue sheets reconstructed by the self-assembly approach from human cells, without the addition of synthetic material or extracellular matrix (ECM), were subjected to mechanical load to induce cell and ECM alignment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 39 publications
1
49
1
Order By: Relevance
“…Furthermore, the microarchitecture of the cell-derived ECM scaffolds can be modulated to achieve different space organization in order to enhance biomimicry. 8,9 Several studies have shown that there is superiority for the application of cell-derived ECM as a scaffold. 4,5,10 The cell-derived ECM can significantly enhance cell adhesion, migration, proliferation, and acquisition of in vivo-like morphology compared with reconstituted ECM.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the microarchitecture of the cell-derived ECM scaffolds can be modulated to achieve different space organization in order to enhance biomimicry. 8,9 Several studies have shown that there is superiority for the application of cell-derived ECM as a scaffold. 4,5,10 The cell-derived ECM can significantly enhance cell adhesion, migration, proliferation, and acquisition of in vivo-like morphology compared with reconstituted ECM.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, tissue engineered grafts made solely from cell-secreted ECM, using a "self-assembly" or cell sheet-based approach, could support high burst pressures and have shown success in vivo, yet lacked the desired organization [14]. However, further refinement of this approach using static mechanical load to align matured cell sheets has resulted in tissues with the desired cell/matrix organization and mechanical anisotropy [15]. These results are extremely encouraging, however, this method requires increasing the already lengthy incubation time in order generate such organization.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] Further, treatment of cell-seeded collagen gels with sodium azide, an ATP inhibitor, or cytochalasin D, a cytoskeletal inhibitor, has been found to inhibit such matrix reorganization following mechanical stimulation. 49,50 Previous work has also correlated increased biomechanical properties in engineered neotissues with increased crosslinks, 38,51 suggesting that the greater functional properties in the middle zone of 10-g-loaded constructs are likely related to the increased crosslink content in this region. Such work indicates that cells, in response to a mechanical input, generate intrinsic traction forces to align compact, and crosslink collagen fibers such that they counter the newly loaded environment.…”
Section: Discussionmentioning
confidence: 96%